The Ability of Different Lignins to Stabilize the Oil-in-water Emulsion - Shulga, Galia; Livcha, Sandra; Neiberte, Brigita; Verovkins, Anrijs; Vitolina, Sanita; Zhilinska, Elina (Advanced Aspects of Engineering Research Vol. 7, 2021)
The ability of aspen soda and wheat straw soda lignin to stabilize the “rapeseed oil-in-water” (O/W) emulsion, depending on the pH value and concentration of the applied water solutions as well as on the lignin chemical composition and molecular mass, and the sizes and zeta potential of lignin particles was studied. It was shown that the O/W emulsion stabilized with the alkaline water solutions of wheat straw lignin demonstrated the highest stability in alkaline medium, while the ability of aspen soda lignin to prevent the coalescence of oil droplets manifested itself in a whole range of the studied pH values. With decreasing pH values of the wheat straw lignin water solution, the drop in the separation volume of the O/W emulsion was insignificant with the exception for the lignin enhanced concentrations in acidic medium. The aggregative stability of the O/W emulsion, which was stabilized with aspen soda lignin, increased with decreasing pH values and increasing lignin content in the emulsion. The findings indicated that the stabilization of the O/W emulsion with the alkaline lignin solutions proceeded via the electrostatic stabilization mechanism, while in the neutral and acidic medium, this mechanism was more complicated, with a growing role of the ability of lignin to form interfacial polymeric films at the liquid/liquid interface. The comparison of the stability of the O/W emulsion showed that aspen soda lignin was a better stabilizer of the O/W emulsion than wheat straw lignin.